Basics of functional integral technique in quantum theory of many-body systems = - Nguyễn, Văn Hiếu (Vietnam National University Publishing House, 1999)
Contents: Non-relativistic fermions; superconducting pairing of fermions on soilds; system of strongly correlated electrons in the lattice.